Prevention of Non-Alcoholic Fatty Liver Disease by Fruits and Vegetables Supplementation in Mice is Associated with Their Antioxidant Property. (29th May 2020) - Guo, Weimin; Wu, Dayong; Li, Lijun; Ortega, Edwin; Liu, Yankun; Thomas, Michael; Nikolova-Karakashian, Mariana; Meydani, Mohsen; Meydani, Simin
Abstract: Objectives: Previously we showed that supplementing a high fat diet (HFD) with a freeze-dried powder of 24 commonly consumed fruits and vegetables (F&V) prevented HFD-induced non-alcoholic fatty liver disease (NAFLD). Since the experimental diets were isocaloric with major difference being in their antioxidant content, we hypothesized that the observed effects of F&V maybe due to their antioxidant property resulting in reduced formation of inflammatory cytokines and lipids such as TNF-α and sphingolipid ceramides. Both TNF-α and ceramides have been implicated as risk factors for NFALD. The objective of this study was to test the above hypothesis. Methods: Six-wk-old male C57BL/6 J mice were randomized to three groups (12/group) to receive one of the following diets: low fat (LF, 10% kcal fat), high fat (HF, 45% kcal fat), and HF plus 15% freeze-dried mixture of F&V (HF + F&V). After 20 weeks, mice were euthanized, blood and liver samples were collected for analyses of cytokines, lipids, and malondialdehyde (MDA), a lipid peroxidation biomarker, and pathways involved in ceramide formation. Results: Mice fed the HF diet had significantly higher liver steatosis and plasma and/or liver ceramides, TNF-α, and MDA compared to those fed the LF diet. However, F&V supplementation prevented HF diet-induced NAFLD and significantly reduced upregulated TNF-α, ceramide, and MDA levels. Because of key role of ceramides in NFALD development, we further determined the mechanism of F&V-induced decrease in ceramide formation focusing on de novo synthesis and activity of sphingomyelinase (SMase), the enzyme that hydrolyzes sphingomyelin to generate ceramide and is modulated by oxidative stress. There was no difference in de novo ceramide synthesis; however, F&V supplementation significantly prevented HF-induced higher SMase activity. Further, liver MDA levels were positively correlated with levels of ceramides, TNF-α, SMase activity, and liver steatosis area. Conclusions: The results from this study suggest that prevention of NFALD by F&V might be mediated through reduction in oxidative stress, consequently suppressing production of pro-inflammatory cytokines, and inhibiting SMase activity that leads to reduction of ceramide levels. Funding Sources: This study was supported by the U.S. Department of Agriculture – Agricultural Research Service (ARS), under Agreement No. 58-1950-4-003.